2002
DOI: 10.1002/jnr.10157
|View full text |Cite
|
Sign up to set email alerts
|

High‐density microarray analysis of hippocampal gene expression following experimental brain injury

Abstract: Behavioral, biophysical, and pharmacological studies have implicated the hippocampus in the formation and storage of spatial memory. Traumatic brain injury (TBI) often causes spatial memory deficits, which are thought to arise from the death as well as the dysfunction of hippocampal neurons. Cell death and dysfunction are commonly associated with and often caused by altered expression of specific genes. The identification of the genes involved in these processes, as well as those participating in postinjury ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
112
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(133 citation statements)
references
References 82 publications
18
112
3
Order By: Relevance
“…Oxidative stress contributes to synaptic dysfunction and disconnection, with impaired mitochondrial transport to the synapses contributing to both neuronal death and neuritic degenerative cascades [15,16]. Exitotoxicity contributes to energy failure resulting in further oxidative stress by enhanced metabolism of excitatory amino acids, leading to secondary cascades of injuries following TBI [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress contributes to synaptic dysfunction and disconnection, with impaired mitochondrial transport to the synapses contributing to both neuronal death and neuritic degenerative cascades [15,16]. Exitotoxicity contributes to energy failure resulting in further oxidative stress by enhanced metabolism of excitatory amino acids, leading to secondary cascades of injuries following TBI [46].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of oxidative stress both the function and transport of mitochondrial to synaptic regions is impaired, decrease synaptic function [15,16], which results in neurodegeneration after brain injury [17,18]. A recent study reported that oxidative stress alters the function of PSD-95 by decreasing a voltage-gated potassium channel that is closely linked to the PSD [19], suggesting that synapse loss and replacement, known to occur following TBI [20], could be modulated by the levels of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of studies that have used microarray analysis of brain homogenates during the past few years to examine gross regional gene expression profiles in rodent models of such complex brain disorders as TBI, stroke, and epilepsy are summarized in Table I, along with the species, conditions, and types of arrays that were used for each comparison. [25][26][27][28][29][30][31][32][33] All five of the TBI studies listed in Table I employed a controlled cortical impact (CCI) model of injury, but different strains and species were used in the different studies. The microarrays most frequently used for all of the rat studies were the Affymetrix U34 Rat Neurobiology array and U34 Rat Genome Set, whereas different arrays were used for each of the mouse studies.…”
Section: Gene Expression Profiling Using Brain Homogenatesmentioning
confidence: 99%
“…Although Kobori et al 28 analyzed gene expression at five intervals between 2 h and 14 days, all of the other studies evaluated relatively acute time points after injury. 28 CCI (male c57/BL6 Cortex (2 h, 6 h, 24 h, 3 days, Incyte GEM 2 cDNA Ipsilateral injured frontal mice, 20 g-27 g) a and 14 days postinjury) microarray chips 6 mm of cortex vs. naive (n ϭ 10 pooled) Matzilevich et al 29 CCI (male Long-Evans Hippocampus (3 h and Affymetrix Rat Genome Ipsilateral injured rats, 250 g-275 g) a 24 h postinjury) U34A GeneChip, aRNA hippocampus vs. sham (T7) amplification (n ϭ 10 were pooled) Rao et al 30 MCAO (male spontaneously Frontoparietal cortex Affymetrix Rat Neurobiology Ipsilateral injured cortex hypertensive rats, 280 g-320 g) b (6 h and 24 h postinfarction) U34 GeneChip vs. contralat. cortex (n ϭ 3 per each of 3 chips per group were pooled) Schmidt-Kastner et al 31 MCAO (male Sprague-Dawly Peri-ischemic cortex Incyte Mouse UniGene 1 Ipsilateral injured cortex vs. rats, 263 g-370 g) b (3 h postinfarction) microarray sham (n ϭ 2 per each of 3 chips per group were pooled) Elliott et al 32 Drug-induced and terminated Dentate gyrus: 14 days after Affymetrix Rat Genome Bilateral dentate gyrus after SE status epilepticus (male status epilepticus (SE) and U34A GeneChip vs. P3 (n ϭ 2 to 3 from adult Sprague-Dawley rats, 180 g-200 g) 3 days postnatal or n ϭ 10 to 12 from P3 animals pooled) Lukasiuk et al 33 Amygdala stimulation with Temporal lobe and hippocampus Research Genetics GF300 Bilateral hippocampus and electrode (male Sprague-Dawley (1 day, 4 days, 1 week, 2 weeks filter cDNA microarrays temporal lobes after SE vs. rats, 290 g-360 g) with seizures and 2 weeks without controls (n ϭ 2 to 3 were seizures after SE) pooled per chip per group) a CCI-Controlled Cortical Impact brain injury.…”
Section: Gene Expression Profiling Using Brain Homogenatesmentioning
confidence: 99%
See 1 more Smart Citation